Fifty Shades of White: Cosmopolitan Whiteness of Korean-Indonesian YouTube Beauty Vloggers - Shafira Bella; Gesang Manggala Nugraha Putra (MOZAIK HUMANIORA, 2026)
This article examines how Korean-Indonesian beauty vloggers Sunnydahye and Han Yoo Ra construct their self-branding on YouTube to appeal to Indonesian audiences, and how their content contributes to the renegotiation of beauty standards in Indonesia. Despite growing scholarship on digital beauty culture in Asia, the role of cross-cultural micro-celebrities in reproducing racialised beauty ideals on YouTube remains underexamined in the Indonesian context. Drawing on Saraswati’s (2013) concept of cosmopolitan whiteness and theories of micro-celebrity, aspirational labour, and aesthetic labour, this study employs textual analysis of the most-watched beauty-related videos on the vloggers’ YouTube channels. The analysis reveals that both vloggers exploit their Korean-Indonesian cultural identities to position themselves as authoritative beauty intermediaries. Their content consistently promotes flawless, lighter skin as the ideal through skincare routines, makeup tutorials, and photo-editing guides, reproducing whiteness under substitute terms such as clear, blemish-free, and glowing. While Sunnydahye attempts to accommodate Indonesia’s cultural diversity, most notably by producing a Korean makeup tutorial for hijab-wearing women, Han Yoo Ra’s tutorials are primarily directed at Peranakan and East Asian communities within Indonesia. Together, their videos reinforce a narrow and racialised vision of feminine beauty, blurring inter-Asian differences while repackaging Korean whiteness as a universally aspirational aesthetic.